Analysis Of Factors Influencing The Performance Of Payakumbuh City Public Housing And Residential Area Employees Using Binary Logistic Regression - Edvidel Arda; Arif Aulia; Jerry Heikal (Jurnal Ekonomi dan Bisnis Digital, 2023)
Housing and Residential Area Service operates efficiently and is able to respond to growing urban challenges. However, in a complex organization like the Department, understanding employee performance and identifying areas that need improvement can be a very complex task. to analyze the factors that influence employee performance at the Public Housing and Settlement Area Service of Payakumbuh City. The method used is binary logistic regression with the dependent variable (Y) being employee performance, while the independent variables are Discipline, Cooperation, Competence, Integrity, Commitment, Performance. From the results of the above analysis there are 2 (two) variables that significantly influence the performance of Housing Department employees People and Residential Areas of Payakumbuh City, namely Competency and Commitment Variables. From the results of binary logistic regression, it is known that there are 36 employees with high performance, while there are 17 employees with low performance.